Adaptasi Guru Pendidikan Agama Islam dalam Digitalisasi Pembelajaran Pasca Pembelajaran Jarak Jauh (Studi Kasus di SMP Negeri 2 Bojong, Kab. Tegal, Jawa Tengah) - Tomi Azami; Basukiyatno Basukiyatno (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2022)
The purpose of this study is to analyze and describe the pattern of adaptation of Islamic Religious Education Teachers (PAI) on the phenomenon of digitalization of learning. The phenomenon of using digital in learning begins with the phenomenon of Distance Learning (PJJ) as a response to the emergence and outbreak of Covid-19 which has become a pandemic in Indonesia. This research uses a qualitative approach with a case study approach. The research locus is at SMP Negeri 2 Bojong. Geographically, SMP Negeri 2 Bojong is located in a mountainous area. The reason for choosing the locus is the peculiarity of the locus because it is located in a mountainous area while digitization is closely related to urban areas. The informant selection technique is purposive sampling, which is selecting informants based on the criteria determined by the researcher. Data collection is done by means of observation, interviews and documentation, the data will be analyzed using Miles and Huberman's interactive analysis technique. The results showed that PAI teachers at SMP Negeri 2 Bojong were fully prepared. The teacher uses the